Multimorbidity and Health-Related Quality of Life in Korean Older Adults: A Mediation Analysis on Handgrip Strength - Jeonghyeon Kim; Inhwan Lee; Haeryun Hong; Hyunsik Kang (Journal of Men's Health, 2022)
Background: The influence of handgrip strength on the relationship of multimorbidity with health-related quality of life (HRQoL) is unknown in geriatric populations. The current study investigated whether or not handgrip strength mediates the association between multimorbidity and HRQoL in a representative sample of Korean adults (3139 men/3753 women) aged 65 years and older. Methods: The data obtained from the 2014–2019 Korea National Health and Nutrition Examination Survey (KNHNES) were used in the current study. The EuroQoL group was used to assess HRQoL. Multimorbidity was defined as co-existence of more than one of the 26 diagnosed diseases specified in the KNHNES. A digital hand dynamometer was used to measure handgrip strength. The covariates included in this study were age, gender, parameters of body fatness, socio-demographics, and parameters of health behaviors. Results: Analysis of variance showed that HRQoL was inversely associated with number of chronic conditions and positively with relative handgrip strength. Particularly, a mediation analysis using the PROCESS macro in SPSS-PC showed that relative handgrip strength partially mediates the influence of multimorbidity on HRQoL. Bootstrapping showed that the indirect effect of comorbidity on HRQoL via relative handgrip strength was significant (p < 0.001) even after adjustments for all the covariates, explaining 8.1% the total effect. Conclusions: The findings of the study emphasize the importance of health-related physical fitness while managing and/or treating multiple chronic conditions for better HRQoL in geriatric populations.